Economic impacts of chronic conditions in a country with high levels of population health coverage: lessons from Mongolia. Issue 6 (1st April 2019) - Dugee, Otgontuya; Sugar, Bolormaa; Dorjsuren, Bayarsaikhan; Mahal, Ajay
Abstract: Objective: To analyse the impact of non‐communicable diseases (NCDs) on household out‐of‐pocket (OOP) expenses, catastrophic health payments and medical impoverishment in Mongolia, a middle‐income country with a high population health insurance coverage rate. Methods: Secondary data analysis of the Mongolian Household Socioeconomic Survey with 12 840 households, including information on standard of living, OOP spending, and health conditions of household members. Measures of catastrophic spending and medical impoverishment were constructed for Mongolia. The association of medical impoverishment and catastrophic spending with a range of socioeconomic and demographic covariates and health conditions was assessed using multiple regression models. Results: OOP health spending contributed to an 8% increase in the incidence of poverty in Mongolia. The impoverishment associated with medical expenses is concentrated in the poorer quintiles, indicating some deepening of poverty among the already poor. Households with a member affected by NCDs and with multiple morbidities were more likely to experience catastrophic spending and medical impoverishment than those with infectious diseases. The main drivers of the financial distress were expenditures incurred for outpatient services, including for diagnostics and drugs. Conclusion: Despite high rates of population health insurance coverage, health expenditures have substantial impoverishing effects in Mongolia, with the impacts being greater among households containing individuals with chronic conditions. Addressing the goal of universal health coverage (UHC) in Mongolia needs attention to the depth of coverage, especially for expenditures on outpatient care and medicines, and targeting the poor effectively. Abstract : Objectif: Analyser l'impact des maladies non transmissibles (MNT) sur les dépenses directes des ménages, les paiements de santé catastrophiques et l'appauvrissement médical en Mongolie, un pays à revenu intermédiaire avec un taux élevé de couverture d'assurance santé de sa population. Méthodes: Analyse secondaire des données de l'enquête socioéconomique sur les ménages mongols auprès de 12.840 ménages, y compris des informations sur le niveau de vie, les dépenses directes et les conditions de santé des membres du ménage. Des mesures des dépenses catastrophiques et de l'appauvrissement médical ont été élaborées pour la Mongolie. L'association entre l'appauvrissement médical et les dépenses catastrophiques à une gamme de covariables socioéconomiques et démographiques et de conditions de santé a été évaluée à l'aide de modèles de régression multiple. Résultats: Les dépenses directes de santé contribuaient à une augmentation de 8% de l'incidence de la pauvreté en Mongolie. L'appauvrissement associé aux dépenses médicales est concentré dans les quintiles les plus pauvres, ce qui indique une aggravation de la pauvreté chez ceux déjà pauvres. Les ménages avec un des membres atteint de MNT et avec des morbidités multiples sont plus susceptibles de connaître des dépenses catastrophiques et un appauvrissement médical que ceux souffrant de maladies infectieuses. Les principales causes de la crise financière étaient les dépenses engagées pour les services ambulatoires, notamment les diagnostics et les médicaments. Conclusion: Malgré des taux élevés de couverture de l'assurance santé de la population, les dépenses de santé ont des effets appauvrissants considérables en Mongolie, les impacts étant plus importants pour les ménages comptant des personnes atteintes de maladies chroniques. Pour atteindre l'objectif de la couverture santé universelle (CSU) en Mongolie, il est nécessaire de porter une attention particulière à l'étendue de la couverture, en particulier pour les dépenses en soins ambulatoires et en médicaments, et cibler efficacement les pauvres.